Network Pharmacology-Based Approach Uncovers the Mechanism of GuanXinNing Tablet for Treating Thrombus by MAPKs Signal Pathway - Wang, Mu-Lan; Yang, Qin-Qin; Ying, Xu-Hui; Li, Yuan-Yuan; Wu, Yang-Sheng; Shou, Qi-Yang; Ma, Quan-Xin; Zhu, Zi-Wei; Chen, Min-Li (Frontiers in Pharmacology, 2020)
Background GuanXinNing tablet (GXNT), a traditional Chinese patent medicine, has been widely used clinically for treatment of thrombus attributing to its effectiveness in inhibiting pro-thrombotic factors. However, the underlying action mechanism of GXNT is little known. Methods In this study, the main compounds in GXNT were determined firstly by liquid chromatography-mass spectrometry (LC-MS), followed by ascertaining their sources. Action targets of the active components were predicted and mapped with target genes related to thrombus, and potential action targets for anti-thrombus of active ingredients were obtained via network pharmacology approach. Through enrichments of GO function and KEGG signaling pathway of the action targets, the networks of active component-target and active component-target-path of GXNT were constructed. Additionally, anti-thrombotic effect of GXNT were evaluated using the rat thrombus model induced by FeCl3, and platelet assay in vitro was for observing anti-platelet aggregation effect and further verifying the predicted results of network pharmacology by Western Blot. Results 15 active ingredients were identified in GXNT, and 83 aciton targets were predicted, 17 of which were antithrombotic targets, possibly participating in various biological processes including response to oxidative stress, positive regulation of blood vessel, etc. Besides, KEGG pathways involved in mutiple signal pathways such as MAPK, PI3K-Akt, Platelet activation. Moreover, pharmacodynamics study found that GXNT could significantly reduce the thrombus length and weight and lower platelet aggregation function, as well as the contents of Fbg and PAI-1. Futhermore, GXNT could significantly increase 6-keto-PGF1α content and regulate the ratio of TXB2/6-keto-PGF1α, but had no effect on TXB2. GXNT could obviously inhibit platelet aggregation at a dose-dependent manner. Herein, thrombus-related MAPKs signaling pathway was selected, and it was found that GXNT could significantly reduce the phosphorylation levels of p38MAPK, ERK and JNK proteins in platelet. Conclusions The study revealed the pharmacodynamic material basis of GXNT and its potential multicomponent-multitarget-multipath pharmacological effects. Moreover, GXNT had antithrombotic effects, the mechanism of which may be related to inhibiting phosphorylation of p38, ERK and JNK proteins in MAPKs signaling pathway, verifying the assumptions of network pharmacology, and providing a strategy for the development and application of GXNT.